Math, asked by strawberrygirl887, 3 months ago

Factorise the polynomial p(x)= 2x^3+x^2-7x-6
2x^3+x^2-7x-6

Answers

Answered by RXMANIT
0

Answer:

f(x) =2x^3+x^2-5x-2x-6 2x^3-2x+x^2-5x-6

2x (x^2-1) +x^2-6x+x-6 2x(x+1) (x-1) +x(x-6) +1(x-6) 2x(x+1) (x-1) +(x-6) (x+1) (x+1) (2x(x-1) +x-6) (x+1) (2x^2-2x+x-6) (x+1) (2x^2-x-6) (x+1) (2x^2-4x+3x-6) (x+1) (2x(x-2) +3(x-2)) f(x) =(x+1) (x-2) (2x+3) root of polynomial in given by (x+1), (x-2), (2x+3) =0 (x=-1, x=2, x=-3/2)

:)

Answered by Luckydancer950
2

Answer:

f(x) =2x^3+x^2-5x-2x-6 2x^3-2x+x^2-5x-6 2x (x^2-1) +x^2-6x+x-6 2x(x+1) (x-1) +x(x-6) +1(x-6) ...

Similar questions